2004
DOI: 10.1074/jbc.m311267200
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Site Interacts with Sp Factors and Up-regulates the NR1 Promoter during Neuronal Differentiation

Abstract: The NR1 gene undergoes induction in neurogenesis mainly via promoter de-repression, and up-regulation during neuronal differentiation by undefined mechanism(s). Here, we show that in the distal region the NR1 promoter has an active NF-B site sharing the consensus with the immunoglobulin (Ig)/human immunodeficiency virus NF-B site. Mutation of this site significantly reduced NR1 promoter up-regulation during neuronal differentiation of P19 cells. Electrophoretic mobility shift assays revealed that P19 nuclei co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 49 publications
3
65
0
1
Order By: Relevance
“…Activation of serum glucocorticoid kinase 1, a downstream target of phosphatidylinositol 3-kinase, increases Grin1 promoter activity in PC12 cells and hippocampal neurons in an NFB-independent manner (Tai et al, 2009). This finding is consistent with a previous report that the Sprelated factors regulate Grin1 promoter activity through occupancy of a putative NFB consensus element ϳ3 kb GLUTAMATE RECEPTOR ION CHANNELS 421 upstream of the GC box in neurons and in cell lines (Liu et al, 2004a).…”
Section: B Kainate Receptors Grik1 To Grik5supporting
confidence: 82%
“…Activation of serum glucocorticoid kinase 1, a downstream target of phosphatidylinositol 3-kinase, increases Grin1 promoter activity in PC12 cells and hippocampal neurons in an NFB-independent manner (Tai et al, 2009). This finding is consistent with a previous report that the Sprelated factors regulate Grin1 promoter activity through occupancy of a putative NFB consensus element ϳ3 kb GLUTAMATE RECEPTOR ION CHANNELS 421 upstream of the GC box in neurons and in cell lines (Liu et al, 2004a).…”
Section: B Kainate Receptors Grik1 To Grik5supporting
confidence: 82%
“…Downstream from the transcription start site, from ϩ43 to ϩ52, a previously unnoted NFB element was identified, which might participate in the Dp71 promoter function. Recently, it was demonstrated that Sp1 and Sp3 transactivate several promoters by interacting directly with NFB-like elements (44,45). Therefore, it is possible that, in the absence of intact consensus Sp DNA-binding sites, Sp1 and Sp3 might act on the Dp71 promoter by binding to the NFB element.…”
Section: Discussionmentioning
confidence: 99%
“…EMSA analysis using a conserved NF-kB binding site revealed that NF-kB binding to DNA was increased both in vivo and in vitro (111), and two different kinds of DNA -protein complexes were formed (112). The formation of protein-DNA complexes was changed either by fasting or insulin.…”
Section: Nuclear Factor-kappa B (Nf-kb)mentioning
confidence: 99%